Nature or nurture : what makes a servant leader? - Cheng, Wai Lai. (2008)
Our research seeks to address the gap by examining two major antecedents to servant leadership: leaders’ personality traits reflecting the “nature” argument, and leaders’ availability of a role model reflecting the “nurture” argument. Given the constant debate on whether leaders are made or born, our research aims to juxtapose the two major perspectives in the context of servant leadership.